Biogeografia histórica das espécies de mamangavas com ênfase nas espécies neotropicais: implicações sistemáticas e para a conservação - José Eustáquio dos Santos Júnior (2017)
Biogeography is a science that uses biological and geographical data to understand the distribution patterns of taxa in a historical and geographical context. Six biogeographical regions are currently recognized in the world with the Brazilian territory integrating the Neotropics. This region presents a complex geological history and constitutes a mosaic of environments with different species assemblages. The search for understanding the geographical and biological processes that resulted in the distribution patterns of Neotropical taxa is hindered by the scarcity of its fossil record and of phylogenetic and phylogeographic studies. Within the context of the biogeographical subregions composing the Neotropics are the eastern Brazilian mountains, which contains a rich variety of soils, climatic microregions and a complex vegetation cover along the altitudinal gradients, which gives these areas a high rate of endemism.Biogeographical methods, phylogenetic analyses and species distribution modelling techniques, the increase in the knowledge on Neotropical bumblebees will contribute to the elucidation of the processes that shaped the distribution of bees in the Neotropics. In this work we use phylogenetic and Biogeographic analyses, based on molecular data, ecological niche models and niche analysis, to understand the processes that shaped the distribution of the Neotropical species of the genus Bombus Latreille, 1802. The first chapter, entitled Hitting an Unintended Target: Phylogeography of Bombus brasiliensis Lepeletier, 1836 and the First New Brazilian Bumblebee Species in a Century (Hymenoptera: Apidae), focuses in the phylogeographic studies of B. brasiliensis and the description of a new bumblebee species with a restricted range between the north of Espírito Santo and south of Bahia. The second chapter, entitled Peripatric speciation followed by niche differentiation between sister bumblebee species from the Atlantic Tropical Rain Forest, Brazil, assess the factors related to the speciation event between B. brasiliensis e B. bahiensis Santos Júnior & Silveira, 2015 and draws attention to the conservation status of B. bahiensis. The third chapter, entitled A new perspective on historical biogeography, divergence times and diversification patterns of Neotropical bumblebees (Hymenoptera: Apidae), compares the rhythm of diversification between the biogeographical regions and aims to comprehend the main processes that shaped the current distribution of bumblebees, with emphasis on the Neotropical region.